The Plan(ner) is Always Changing: Self-directed Funding for Children with Hearing Loss. (2nd July 2016) - Simpson, Andrea; Stewart, Lauryn; Douglas, Jacinta
Abstract: This study investigated the experience of families with young children with hearing loss participating in a self-directed funding scheme in Australia. Eleven hearing caregivers, one male, participated in qualitative semi-structured interviews. Analysis was undertaken using a phenomenological inspired thematic analysis approach. Major themes arising were: a perceived transfer of responsibility from the 'system' to the 'family' in order to get the best outcome for their child, an acknowledgement of having to be prepared for the planning session in order to make a strong case for resources, a sense of disappointment at a perceived lack of interest by staff in the individual circumstances of their child, as well as the challenges of dealing with information overload. The opportunity to engage with a trusted source prior to engaging with self-directed schemes as well as presenting information in a 'just in time' format may assist future families in navigating funding challenges for their child.